Gonadotropin-Secreting Pituitary Macroadenoma Complicated With Hemorrhagic Apoplexy in 18F-FDG PET/CT. (September 2021) - Dejust, Sebastien; Decoudier, Benedicte; Higel, Brigitte; Litre, Claude-Fabien; Morland, David
Abstract : Abstract: We report the case of 69-year-old man referred for a stage IV pulmonary adenocarcinoma and presenting a decrease in visual acuity. An 18 F-FDG PET/CT showed an intense and heterogeneous uptake of a mass in the sellar region. An MRI showed a pituitary macroadenoma associated with a large cyst on the left side, with necrosis zones and fluid level, compressing the optic chiasma. Endocrine testing showed a panhypopituitarism, and pathology confirmed a pituitary apoplexy in a gonadotropin-secreting macroadenoma. No malignant cells were detected. Molecular imaging could have an important role in the detection and characterization of pituitary tumors.